Fabrication and characterization of biomaterial film from gland silk of muga and eri silkworms1. Issue 5 (20th February 2013) - Dutta, Saranga; Talukdar, Bijit; Bharali, Rupjyoti; Rajkhowa, Rangam; Devi, Dipali
Abstract This study discusses the possibilities of liquid silk (Silk gland silk) of Muga and Eri silk, the indigenous non mulberry silkworms of North Eastern region of India, as potential biomaterials. Silk protein fibroin of Bombyx mori, commonly known as mulberry silkworm, has been extensively studied as a versatile biomaterial. As properties of different silk‐based biomaterials vary significantly, it is important to characterize the non mulberry silkworms also in this aspect. Fibroin was extracted from the posterior silk gland of full grown fifth instars larvae, and 2D film was fabricated using standard methods. The films were characterized using SEM, Dynamic contact angle test, FTIR, XRD, DSC, and TGA and compared with respective silk fibers. SEM images of films reveal presence of some globules and filamentous structure. Films of both the silkworms were found to be amorphous with random coil conformation, hydrophobic in nature, and resistant to organic solvents. Non mulberry silk films had higher thermal resistance than mulberry silk. Fibers were thermally more stable than the films. This study provides insight into the new arena of research in application of liquid silk of non mulberry silkworms as biomaterials. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 292–333, 2013.